Pengembangan Kurikulum PAI di Madrasah - Nur Azizah Ashari (STAI Bumi Silampari, 2021)
This research is a research that contributes ideas in developing curriculum in Madrasah. This is because the progress of the times has penetrated all areas of life, including the field of education. Ofcourse the progress of the times demands progress that affects all aspects in it, including the curriculum as a reference in the education process. So there is a need for curriculum development, especially in Madrasas which in fact prioritize religious education in it. This is of course related to the demands of the times for graduates from Madrasas to be able to compete and not be out of date. The method in this study uses qualitative research and the type of research is library research. The results of this study are the curriculum development process includes: Determining the Model in Development, analyzing Needs and Situations, Determining Objectives, Goals, Goals, Formulating Content in the Curriculum, Selecting Methods in Developing Curriculum, Evaluating Curriculum, Implementing Curriculum, Curriculum Changes Providing Feedback.